Bronchitis and Its Associated Risk Factors in First Nations Children - Chandima Karunanayake; Donna Rennie; Vivian Ramsden; Mark Fenton; Shelley Kirychuk; Joshua Lawson; Raina Henderson; Laurie Jimmy; Jeremy Seeseequasis; Sylvia Abonyi; James Dosman; Punam Pahwa; et al. (Children, 2017)
Respiratory diseases, such as bronchitis and pneumonia, are common in First Nations children in Canada. The objectives are to determine prevalence and associated risk factors of bronchitis in children 6–17 years old residing in two reserve communities. The cross-sectional study was conducted in 2013 and children from two First Nations reserve communities participated. The outcome was ever presence/absence of bronchitis. Logistic regression analysis was conducted to examine the relationship between bronchitis and the individual and environmental factors. A total of 351 First Nations children participated in the study. The prevalence of bronchitis was 17.9%. While 86.6% had at least one parent who smoked, smoking inside home was 43.9%. Signs of mold and mildew in homes were high. Prevalence of houses with any damage caused by dampness was 42.2%, with 44.2% of homes showing signs of mold or mildew. Significant predictors of increased risk of bronchitis were: being obese; having respiratory allergies; exposed to parental cigarette smoking; and signs of mold and mildew in the home. There are several modifiable risk factors that should be considered when examining preventive interventions for bronchitis including obesity, smoking exposure, and home mold or dampness.